Law for business - Barnes, A. James (McGraw Hill, 2006)
For over 20 years, Law for Business has gone well beyond merely identifying the current legal rules and regulations affecting business by offering insights into new developments and trends that will affect the future of business. It has provided students with a comprehensive, yet concise treatment of the legal issues of fundamental importance to business students and the business profession. The cases, which have always been a strong feature, are edited and re-written by the authors, who divide the material into three categories: facts, issues, decisions. The authors, Barnes, Dworkin, and Richards, choose cases that are appropriate to explain precedent and history as well as include "hot topic" cases that relate to current events. In addition to case applications, the authors use such techniques as content summaries to apply concepts to practice. Effective managers and employees must develop knowledge of both law and business because people involved in business also are involved in, and greatly affected by, the laws concerning business..